2016
DOI: 10.4274/mirt.22932
|View full text |Cite
|
Sign up to set email alerts
|

Hypermetabolic Calcified Lymph Nodes on 18Fludeoxyglucose-Positron Emission Tomography/Computed Tomography in a Case of Treated Ovarian Cancer Recurrence: Residual Disease or Benign Formation?

Abstract: The contribution of positron emission tomography/computed tomography (PET/CT) with 18F-fludeoxyglucose (FDG) in evaluating ovarian cancer recurrence even after a prolonged disease-free interval, and in therapy response is well-described. Calcifications observed in CT, although usually attributed to benign conditions, may actually represent active disease. Such an example of calcified formations is psammoma bodies. We present a case of 56-y. o. patient with ovarian cancer relapse at the supraclavicular area 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…Studies also reported that retrocrural lymph node metastases are associated with supradiaphragmatic lymph node involvement [77,78]. Retrocrural lymph nodes have recently been discovered for OC surgery [77,79]. However, there remains a need and potential for greater awareness of this space, relevant to surgical dissection and lymph node assessment.…”
Section: Retrocrural Lymph Nodesmentioning
confidence: 99%
“…Studies also reported that retrocrural lymph node metastases are associated with supradiaphragmatic lymph node involvement [77,78]. Retrocrural lymph nodes have recently been discovered for OC surgery [77,79]. However, there remains a need and potential for greater awareness of this space, relevant to surgical dissection and lymph node assessment.…”
Section: Retrocrural Lymph Nodesmentioning
confidence: 99%